(untitled) (Communication & Society, 2019)
This article explores the application of the concept of transmedia narrative to the construction of the public image of political figures, in a media context characterised by the prevalence of infotainment and the dissolution of the boundaries of political content. To attain this objective, a case-study on a specific leader is carried out; he is a regional leader recognised at a national level thanks to his discursive strategy: president of Cantabria, Miguel Ángel Revilla, chosen for his role as a regular guest on T.V shows of all kinds, as well as for having become the third most followed Spanish politician on social networks. Through content analysis, we examine the character’s own performance on different media (television, social networks and an autobiographical book) along with the reactions provoked among the cybernauts. The results show a multiplatform narrative adapted to the specific formal language of each of those media and formats, constantly maintaining the application of politainment features (personalisation, entertainment, emotiveness and trivialisation of the issues). Regarding the effects, there is a high level of involvement and a love-hate dichotomy among the public, as proved in social networks. Consequently, in the transmedia political narrative (TPN) the users co-create the resulting image of the politician who is finally perceived by the audience. In addition, the success of Revilla’s communication strategy is verified via ensuring that the self-assigned values in his speech, such as leadership and closeness to the people, match those that the audience identify with his figure.